BOSHLANG'ICH SINFLARDA YANGI PED TEXNOLOGIYALAR VA INAVATSION METODLARDAN FOYDALANISH VA O'QITISH METODIKASI - Nazarova Gulmira Nabijonovna (PEDAGOGS, 2024)
Annotation: The article provides information on the use of modern innovative methods and their types in teaching primary school students. They also talked about their importance today